دور المقاولة الصغيرة والمتوسطة في تحقيق التنمية الاقتصادية في الجزائر ببرج بوعريريج POLYBEN عرض تجربة مؤسسة - برحومة, عبد الحميد; مهديد, فاطمة الزهراء (Université de M'sila, 2012)
يتفق الكثير من الاقتصاديين على أن دعم ومساندة إنشاء المؤسسات الصغيرة والمتوسطة من أهم روافد عملية التنمية الاقتصادية والاجتماعية، وذلك باعتبارها منطلقًا أساسيًا لزيادة الطاقة الإنتاجية وترقي الصادرات من ناحية، والمساهمة في معالجة مشكلتي الفقر والبطالة من ناحية أخرى. ولذلك أولت دول كثيرة اهتمامًا متزايدًا بهذه المشاريع وقدمت لها العون والمساعدة بمختلف السبل ووفقًا للإمكانيات المتاحة. وتهدف هذه الورقة إلى التعرف على مدى مساهمة المؤسسات المقاولة الصغيرة والمتوسطة في تحقيق التنمية الاقتصادية في الجزائر، حيث تتضمن الدراسة عرضا نظريا لمفهوم المقاولة الصغيرة والمتوسطة، إضافة إلى عرض نموذج لهذه المؤسسات والمتمثل في تجربة ببرج بوعريريج. POLYBEN مؤسسة
Abstract Many economists have agreed that the support of the establishment of small and medium enterprises is the most important tributaries of the process of economic and social development. It is considered as an essential starting point to increase production and the promotion of exports on one hand, and to contribute in addressing the problems of poverty and unemployment on the other. Therefore, many countries have given a growing interest in these projects and provided help and assistance in various ways, within their available possibilities. This paper aims to identify the contribution of small and medium enterprises in economic development in Algeria, where the study will include a presentation of the concept of entrepreneurship theory, small and medium enterprises, as well as the case of POLYBEN as model of these enterprises.
Keywords: المقاولة، روح المقاولاتية، المؤسسات الصغيرة والمتوسطة، التنمية الاقتصادية.( Entrepreneurship, Entrepreneurial Spirit, Small And Medium Enterprises, Economic Development )